Isolation and identification of bacteria from mobile phones of students and employees of Hajee Mohammad Danesh Science and Technology University, Bangladesh - Hussein, Zakarie Ahmed; Hossain, Md Khaled; Rumi, Nazmi Ara; Rahman, Md Shajedur; Kundu, Tonmoy; Mohamed, Abdisalan Abdullahi (Asian Journal of Medical and Biological Research, 2020)
Microbes are capable to survive on mobile phone surface and serve as a potential transporter of microorganism amongst handlers. Thus, the study focused on isolation and identification of bacteria from mobile phones of academic and non-academic staffs (including students and cleaners) of Hajee Mohammad Danesh Science and Technology University Dinajpur, Bangladesh. A total of 32 swab samples of mobile phones were collected. The bacteria isolates were identified on the basis of morphological, cultural and biochemical characterization. The total viable count (TVC) of different swab samples of mobile phones in different categories were ranged from 73×10-6 CFU/ml to 260×10-6 CFU/ml. Analysis revealed that, among the samples 21 (25.6%) isolates were Staphylococcus spp, 17 (20.7%) were Bacillus spp, 16 (19.5%) were Klebsiella spp, 15 (18%) were Pseudomonas spp and 13 (15.85%) were Salmonella spp. Additionally, antibiotic sensitivity test revealed the bacteria isolates were resistant to Penicillin, Amoxicillin, Cefaclor, Ofloxacin and Ciprofloxacin. The findings suggest that all the samples under observation were highly susceptible to a number of microbes belongs to the natural flora of human body. Hence, it is encouraged to avoid mobile phone handling while eating. Last but not the least, personal hygiene is highly recommended, as mobile phone can be a potential source of disease transmission. Asian J. Med. Biol. Res. September 2020, 6(3): 570-576